The Relationship Between Law and Public Policy in Social Development - Sutrisno, Endang (Politeknik Siber Cerdika Internasional, 2025)
Law and public policy play a fundamental role in shaping social development by providing the legal framework and governance mechanisms that regulate economic, political, and social interactions. In modern democracies, the relationship between law and public policy is crucial in addressing societal challenges such as inequality, economic growth, and human rights protection. However, discrepancies between legal frameworks and public policies can hinder effective governance and social progress. This research examines how law influences public policy formulation and implementation in the context of social development, identifying key challenges and proposing strategies for enhancing legal and policy coherence. This study employed a qualitative research approach, utilizing a comparative analysis of legal frameworks, policy-making processes, and case studies from various jurisdictions. Data is collected from legal documents, government policies, scholarly articles, and expert opinions. The findings revealed that effective social development requires a strong alignment between legal frameworks and public policy goals. Legal rigidity, political interference, and inconsistent enforcement mechanisms often create barriers to successful policy implementation. On the other hand, well-integrated legal and policy mechanisms contribute to improved governance, economic stability, and social welfare. This research concludes that strengthening the synergy between law and public policy through transparent legal processes, institutional reforms, and inclusive policy making can enhance social development outcomes. The findings contribute to academic discussions on governance, law, and social progress, offering valuable insights for policymakers and legal scholars